Geology of slopes in the Crocker Range, Sabah, Malaysia (Journal of Nepal Geological Society, 2006)
Slope failures are frequent occurrences along roads in Malaysia. Not until recently, geological inputs were rarely sought when designing and constructing roads on mountainous areas. This paper highlights the result of a geological study on selected slopes along a major road across Sabah's main mountain range, the Crocker Range, which is comprised mostly of folded Eocene sedimentary rocks. A total of 48 slopes facing potential failure problems were studied. The following four main potential sources of failures were recognised: 1) related to intensely sheared mudstones within a localised fault zone; 2) related to unfavourable orientation of discontinuity planes whereby bedding and joint planes of sandstone beds occur parallel or sub-parallel to the slope face; 3) related to the presence of intensely fractured and sheared sandstone and mudstone beds within a regional fold hinge; and 4) related to the presence of old landslide deposits. The recommendations to stabilise problematic slopes include covering the unstable slope face with concrete or vegetation and cutting back the slopes further.